Loneliness and life satisfaction in old age: The moderating effect of executive functions - Pekić, Jasmina; Kodžopeljić, Jasmina; Milovanović, Ilija (Psihološka istraživanja, 2024)
S  Satisfaction with life in old age, as well as with the previously achieved life goals, is marked as a prominent factor in successful ageing, i.e. maintaining psychological well-being in old age. On the other hand, in a wide range of challenges that individuals face in late life, the relevant literature especially highlights loneliness, which is considered as an undermining factor of life satisfaction. In order to examine the variety of connections of cognitive variables with loneliness and thereby contribute to the quality of ageing, the research aims to examine the moderating role of working memory and inhibitory control in the relationship between socioemotional loneliness and a general assessment of life satisfaction in old age. The research was conducted on a sample of 198 respondents (65.7% women) over the age of 65 (M = 75.38, SD = 7.13) from the territory of Vojvodina, Republic of Serbia. The following instruments were used to measure the variables of interest: the De Jong Gierveld Loneliness Scale (DJGLS), the Adult Executive Functioning Inventory (ADEXI) and the Satisfaction With Life Scale–3 (SWLS–3). The obtained results indicate that, in the elderly with higher efficiency of working memory, lower ability of inhibitory control leads to loneliness, which has significant negative effects on life satisfaction. On the other hand, in the older people with lower working memory efficiency, the level of inhibition ability does not significantly determine the relationship between loneliness and life satisfaction.